2013
DOI: 10.1071/fp13149
|View full text |Cite
|
Sign up to set email alerts
|

Water: the most important ‘molecular’ component of water stress tolerance research

Abstract: Abstract. Water deficit is the main yield-limiting factor across the Asian and African semiarid tropics and a basic consideration when developing crop cultivars for water-limited conditions is to ensure that crop water demand matches season water supply. Conventional breeding has contributed to the development of varieties that are better adapted to water stress, such as early maturing cultivars that match water supply and demand and then escape terminal water stress. However, an optimisation of this match is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 115 publications
4
95
1
2
Order By: Relevance
“…This growth characteristic is an adaptation to water-limiting conditions, and it is crucial for the formation of the aerial portion of the plant (Hsiao and Xu, 2000;Sharp and Davies, 1979;Westgate and Boyer, 1985;Yamaguchi and Sharp, 2010). Several authors have concluded that, in maize plants, the root architecture, length and water extraction are closely related; however, other studies have shown poor relationships between water uptake and root length and density compared with other crops, such as chickpea and lentil (Valdez et al, 2013). When exposed to water deficit conditions, the elongation zone of the maize radicle has the capacity for osmotic adjustment, and an increase of 45% in the proline concentration has been observed Voetberg and Sharp, 1991).…”
Section: Introductionmentioning
confidence: 96%
“…This growth characteristic is an adaptation to water-limiting conditions, and it is crucial for the formation of the aerial portion of the plant (Hsiao and Xu, 2000;Sharp and Davies, 1979;Westgate and Boyer, 1985;Yamaguchi and Sharp, 2010). Several authors have concluded that, in maize plants, the root architecture, length and water extraction are closely related; however, other studies have shown poor relationships between water uptake and root length and density compared with other crops, such as chickpea and lentil (Valdez et al, 2013). When exposed to water deficit conditions, the elongation zone of the maize radicle has the capacity for osmotic adjustment, and an increase of 45% in the proline concentration has been observed Voetberg and Sharp, 1991).…”
Section: Introductionmentioning
confidence: 96%
“…However, laboratory conditions are substantially different from the actual field and hence, improved plant survival under PEG-induced drought may not always correlate with the gains in the field. Moreover, antioxidative defense have shown to occur at much later stage of stress tolerance in field crops such as Cicer arietinum, Arachis hypogaea and Pennisetum glaucum, bearing no correlation with the actual yield under drought[88]. Nevertheless, the influence of NO on stomatal closure is indeed beneficial for maintaining plant water status, and hence holds relevance.…”
mentioning
confidence: 93%
“…Water uptake into the cells is regulated by aquaporin protein channels located in the plasma membrane of root hair cells (Agre et al 1993;Tyerman et al 2002) and can be determined by a lysimetric method. The application of lysimetric method in sorghum revealed a large genotypic variation in water extraction capacity from the soil profile and can also be used for a gravimetric screening of transpiration efficiency (TE) (Vadez et al 2008(Vadez et al , 2011(Vadez et al , 2013Vadez 2014). The method can also be applied to other cereals such as wheat and barley.…”
Section: Plant Physiological Mechanisms Associated With Drought Resismentioning
confidence: 99%
“…the given genetic material cannot adopt all of them. As the most crucial example, the "trade-off " principle between water conservation and biomass accumulation as expressed in terms of WUE and EUW can be given (Tardieu 2012;Vadez et al 2013). Therefore, knowledge of the environment (a season when drought occurs and the severity of the drought stress) appears to be crucial in the selection of the most suitable breeding strategy.…”
Section: Breeding Approaches To Improve Drought Resistance In Barley mentioning
confidence: 99%